Dożynki. (Gdynia : [s.n.], 1949)
Afisz inf. o dożynkach wraz z programem, które miały w Rumi 11.09.1949 r.
Keywords: Święta rolnicze -- Polska -- Rumia -- 1945-1970 -- druki ulotne; Rumia (Polska) -- 1945-1970 -- druki ulotne; Rumia (Polska) -- 1945-1970 -- źródła